A Leap Into the Unknown – Early Events in African Trypanosome Transmission. Issue 3 (March 2020) - Szöőr, Balázs; Silvester, Eleanor; Matthews, Keith R.
Abstract : African trypanosomes are mainly transmitted by tsetse flies. In recent years there has been good progress in understanding how the parasites prepare for transmission, detect their changed environment through the perception of different environmental cues, and respond by changing their developmental gene expression. In this review, we discuss the different signals and signaling mechanisms used by the parasites to carry out the early events necessary for their establishment in the fly. We also compare Trypanosoma brucei and Trypanosoma congolense, parasites that share a common pathway in the early stages of fly colonization but apparently use different mechanisms to achieve this. Highlights: African trypanosomes are mainly transmitted by tsetse flies. During uptake in a blood meal, T. brucei can use several potential environmental cues to stimulate the initiation of differentiation. Signal transduction involves a phosphatase signaling cascade and spatial control of key regulatory proteins. Once differentiation is initiated, several gene regulatory processes control the differentiation from bloodstream to tsetse midgut procyclic forms. T. brucei and T. congolense show a similar route of establishment in the tsetse gut but show different developmental mechanisms.